THE ROLE OF AI TOOLS IN ENHANCING ANALYTICAL AND CRITICAL THINKING SKILLS IN UNIVERSITY STUDENTS - Gʻayrat Muxtorovich Sultonqulov (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract In the rapidly changing landscape of higher education, the integration of Artificial Intelligence (AI) tools presents a transformative opportunity to boost students’ analytical and critical thinking skills. This article elucidates the various AI applications utilized in universities, their impact on learning outcomes, and the pedagogical strategies that can be deployed to maximize their effectiveness. By examining case studies, theoretical frameworks, and empirical research, this article aims to provide a comprehensive overview of how AI tools can support the development of essential skills necessary for success in an increasingly complex world.